Strategi Organisasi Bantuan Hukum dalam Penyerapan Anggaran BantuannHukum Kementerian Hukum dan HAMdi Jawa Tengah dan Daerah Istimewa Yogyakarta Tahun 2016 - Faisal Luqman Hakim (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2018)
Law Number 16 of 2011 concerning Legal Aidmandates the government's obligation to provide legalaid funds to disadvantaged communities. To be able tochannel these funds, the Ministry of Law and HumanRights collaborates with Legal Aid Organizations (OBH)throughout Indonesia. There are more than 500 OBHspread throughout Indonesia. As many as 40 (forty)OBH are found in Central Java and 19 (nineteen) OBHare in the Special Region of Yogyakarta. The existingOBH is also required to make various efforts so thatlegal aid funds can be maximally absorbed. Thisresearch was conducted to find out how and thestrategies carried out by OBH in absorbing legal aidfunds by the Ministry of Law and Human Rights inCentral Java and the Special Region of Yogyakarta.From the research conducted, it was found that inabsorbing OBH legal aid funds in Central Java and DIYconducted 1. Recruitment and collaborating withexisting university alumni as well as, 2. Conductinglegal counseling in collaboration with CommunityService Agencies and students , especially for OBHunder the University 3. Cooperation or communication,both formally (based on the MoU) and non-formal (oralcommunication) between OBH and the JudicialInstitution. 4. Conduct legal socialization through massmedia, such as newspapers and radio, and 5. Make useof its own network of members to provide assistance tothe poor justice seekers.